2007
DOI: 10.1007/s00464-007-9710-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic sphincterotomy and interval cholecystectomy are reasonable alternatives to index cholecystectomy in severe acute gallstone pancreatitis (GSP)

Abstract: This study demonstrates that overall 62% (22 endoscopic sphincterotomy and 40 index cholecystectomy) of patients with GSP have definitive therapy during the Index admission. However, surgery was deferred in the majority (n = 30) of patients with severe GSP, and 19/30 underwent ES prior to discharge. ES and interval cholecystectomy in severe GSP is associated with minimal morbidity and readmission rates, and is considered a reasonable alternative to an index cholecystectomy in patients with severe GSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 23 publications
(22 reference statements)
1
27
0
Order By: Relevance
“…The papillary muscle function of almost all patients with cholesterol stones is thought to be normal. Therefore, some reports recommended endoscopic papillary balloon dilatation (EPBD) or surgical lithotomy to preserve papillary function and reduce the rate of recurrent CBDS [5]. But in this study, the rate of recurrent CBDS after ES in patients with cholesterol CBDS and gallbladder stones was 0% and that in patients with cholesterol CBDS was 4.4%; these rates were lower than those in patients with bilirubinate stones (13.5%).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The papillary muscle function of almost all patients with cholesterol stones is thought to be normal. Therefore, some reports recommended endoscopic papillary balloon dilatation (EPBD) or surgical lithotomy to preserve papillary function and reduce the rate of recurrent CBDS [5]. But in this study, the rate of recurrent CBDS after ES in patients with cholesterol CBDS and gallbladder stones was 0% and that in patients with cholesterol CBDS was 4.4%; these rates were lower than those in patients with bilirubinate stones (13.5%).…”
Section: Discussionmentioning
confidence: 58%
“…We previously reported that an acalculous gallbladder preserved after ES did not cause major complications [2], and thus preserving an acalculous gallbladder after ES has become a standard practice [3]. In patients with cholecystocholedocholithiasis, however, untreated gallbladder stones are generally thought to be a risk of biliary complications after ES like acute cholecystitis or migration into the CBD; therefore, some authors recommend cholecystectomy because of the high risk of recurrent biliary symptoms [3][4][5][6]. In two recent prospective studies cholecystectomy after ES was justified, because patients with gallbladder in situ had late biliary complications more frequently than cholecystomized patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the cholecystectomy is delayed until the patient has recovered and undergoes an interval elective cholecystectomy [42]. In patients who survive a severe episode of gallstone AP and are not fit enough for surgery, there is a trend to perform an endoscopic sphincterotomy as a definitive procedure on the basis that it reduces the risk of recurrent acute pancreatitis [43]. If these patients develop symptoms of biliary colic, an interval cholecystectomy will be required [44].…”
Section: Surgical Treatment Of Gallstonesmentioning
confidence: 99%
“…The median length of stay of patients following ERCP was 2 days (range, 1-49; IQR, 1-7) with a median total length of stay of 11.5 days (range, 4-85; IQR, [8][9][10][11][12][13][14][15][16][17][18][19][20]. One ERCP and ES was complicated by pancreatitis post-procedure which extended the hospital stay by 30 days.…”
Section: Ercp and Es Alonementioning
confidence: 99%
“…7 The benefits of early endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic sphincterotomy (ES) in acute severe pancreatitis compared with no treatment 8,9 and the role of ERCP and ES in preventing recurrence of pancreatitis prior to interval cholecystectomy have been well documented. 10,11 Despite the benefit of ERCP in acute cases, cholecystectomy is still recommended in the UK within 2 weeks of their pancreatitis. 12 In an ageing population with increased comorbidities however, this treatment is not always appropriate.…”
Section: Introductionmentioning
confidence: 99%